Assessing the Effects of Marine Protected Areas on Biological Invasions: A Global Review - Giakoumi, Sylvaine; Pey, Alexis (Frontiers in Marine Science, 2017)
Marine protected areas (MPAs) have proven to be an effective tool to conserve marine biodiversity and restore ecosystem functioning. Yet, the role of MPAs in providing resilience to global threats, such as biological invasions, is poorly understood. Assessing the effects of MPAs on invasive species is crucial for effective MPA planning and management . We conducted a peer-reviewed literature survey to synthesize all available information on the performance of alien/invasive species in MPAs at a global scale. We also assessed the effects of protection on such species following a meta-analytical approach. We found only 17 studies that were suitable for the qualitative and quantitative synthesis. We included studies that provided data on alien species from both inside and outside MPAs. The largest proportion of the available literature provided data on alien molluscs (40%), followed by algae (28%). Information on the effects of protection on alien/invasive species is available for only 11% of the marine biogeographic provinces; principally, for the Mediterranean and Caribbean Seas. Only four studies provided adequate quantitative data to estimate the effect of protection on the density and biomass of 12 alien species. We found that protection had a significant negative effect on half the species, whereas 33% of the species were positively affected. Our review demonstrates the scarcity of data on this crucial topic. More evidence on various species and taxonomic groups across marine regions is necessary to draw robust conclusions.